Case Report: Acute Bulbar Palsy Plus Syndrome: A Guillain-Barré Syndrome Variant More Prone to Be a Subtype Than Overlap of Distinct Subtypes - Cao, Qian; Chu, Hong; Fu, Xiujuan; Yao, Jiajia; Xiao, Zheman; Lu, Zuneng (Frontiers in Neurology, 2020)
Objective: Acute bulbar palsy plus (ABPp) syndrome is a rare regional variant of Guillain-Barré syndrome (GBS) characterized by acute bulbar palsy combined with other cranial symptoms or ataxia without limb and neck weakness. We aim to investigate characteristics of ABPp syndrome and analyze its nosological position within the GBS spectrum. Methods: A patient with ABPp syndrome was reported and previous case reports of patients who met the criteria for ABPp syndrome from literature were reviewed. Results: A total of 28 patients were included in our study. Median age was 32 years. Most of the patients (78.6%) were from Asia and 75.0% had preceding infection. The main accompanying symptoms were ophthalmoplegia (85.7%), facial palsy (60.7%) and ataxia (50.0%). There existed asymmetric weakness in the form of unilateral facial palsy (32.1%) and ptosis (3.6%). Approximately half of patients had albuminocytological dissociation. All the tested patients were seropositive for anti-ganglioside antibodies, of which the two most common were IgG anti-GT1a (77.3%) and anti-GQ1b (59.1%) antibodies. Over one-third of the patients who underwent electrophysiological assessment showed subclinical neuropathy beyond cranial nerves. The outcome was generally favourable as 89.3% of patients made full recovery within 5 months. Conclusion: The hitherto largest case series of ABPp syndrome advances our understanding of this disease. Serologically, the presence of IgG anti-GT1a and anti-GQ1b antibodies predicts and contributes to the disease. Phenotypically, ABPp syndrome is more prone to be a separate subtype of GBS than overlap of distinct subtypes, and has the potential to complement current diagnostic framework of GBS.